Museums: Accessibility to visitors with visual impairment - Dimitrova Radojichikj, Daniela (My University, 2017)
The purpose of museums is to enable all visitors to enjoy its collections and to learn. Although programs for visitors with visual impairment have appeared in developed countries, it does not seem that much has been done to integrate this group into the museum audience. Museum staff had to consider the different learning needs of visitors and consult with members of the community to gain a better understanding of what needs to be changed in order to make their museum accessible to visitors with different abilities. However, it has also been suggested that inclusive practices can be achieved through the use of Universal Design. According to McGinnis (2007), Universal Design means that exhibitions and programs would have to be designed so that everyone was able to use them. This article aims to analyze the accessibility of museums in Skopje to visitors with visual impairments, with a particular focus on how they can become more inclusive.
Keywords: visitors with visual impairment, museums, accessibility, accessible tourism, museum staff